Myofascial pain at post-sternotomy patients after cardiac surgery: A clinical study in 1226 patients - (:unkn) unknown (IOS PRESS, 2008)
Background and objective: Sternotomy is a major type of surgery, and incidence, characteristics and clinical course of post-sternotomy pain are not well known. Myofascial pain also can occur according to sternotomy. So, the aim of this study was to investigate the incidence of myofascial pain and causative factors at post-sternotomy patients in different kind of cardiac surgeries. Methods: This study was performed between the years 2006-2007 at the Department of Cardiothoracic Surgery in Istanbul Kartal Kosuyolu Yuksek Ihtisas Hospital. 1226 patients over 18 years old were evaluated for myofascial pain. Trigger points in both upper trapezius, and both pectoralis major were identified according to Simons and Gerwin diagnostic criteria (tenderness in a hyper sensible spot within a palpable taut band, local twitch response elicited by snapping palpation, and elicited referred pain with palpation). Myofascial pain evaluation again was performed with the same pain physician at all examination periods. Results: When results were evaluated statistically, of the 1226 total patients, only in 194 (15.8%) patients trigger points were determined. When patients who were determined to have trigger points, it was observed that 135 had undergone CABG. These 135 patients were evaluated in 2 groups; those LIMA used and those where LIMA not used. In 102 patients who underwent CABG where LIMA were used (n = 102, 75.5%). Especially of those 194 patients majority suffered from the muscle groups in the left side more than in right side in terms of trigger point formation. Besides that we have determined a parallel relation between the operation duration and trigger point formation that was statistically significant. Conclusion: As a conclusion, the formation of trigger point in upper trapezius and pectoralis major muscles in patients going under CABG with LIMA is 31.9% in patients postoperatively. We believe the reason for this incident is the graft harvesting of the internal mammary artery. Besides we believe that there is a parallel relation between the operation duration and trigger point formation, and more prospective studies are needed to state the relation between the formation of trigger points and the duration of the CABG.
Keywords: Sternotomy; myofascial pain; pectoralis major; upper trapezius; COMPLICATIONS; FRACTURES; INJURY